AS PERCEPÇÕES DO COORDENADOR PEDAGÓGICO FRENTE AO SEU PAPEL PROFISSIONAL - Silva, Liliane (2020)
This work tries to present, through reports of experiences of educational coordinator, the understanding of these on the importance of the coordinator in the school. We took as a methodology the qualitative approach, which happened from focus groups in order to obtain depth in the questions worked, where six pedagogical coordinators of the Municipal Network of Teaching of Itaperuna / RJ participated in three moments in group, based on wheels of directed conversations, aiming to gather data focused on the discussion of specific topics. Through the reports of the coordinators we can verify that they have a good perception of their work, expressing through their statements how much they consider their essential work in schools, however we could perceive feelings of anguish, immediacy and incompetence for not meeting all the demands schools.